Low Public Perspective on The Importance of a Sustainable Environment in The Environmental Journalism Polemic - Rizqiani, Wiwit; Hidayat, Nurul (International Journal of Environmental Communication (ENVICOMM), 2023)
Forest fires in Indonesia occur continuously every year, but coverage of these events has not been popular in the mass media. The purpose of this study was to identify the understanding of kumparan reporters about environmental journalism based on their knowledge and experience in reporting forest fires. To achieve this goal, this study uses an interpretive paradigm, a qualitative research approach, the unit of analysis chosen is the individual (kumparan reporter), data collection techniques are carried out with in-depth interviews (primary data) and reporting documentation written by the kumparan reporter (secondary data), Data analysis techniques are performed by reducing data, presenting data, and drawing conclusions. The concepts in this research are environmental journalism, reporters as news agents, reporters' understanding of reporting issues, and environmental journalism problems. A reporter' who understands in reporting forest fires is a reporter who knows the ideal coverage in accordance with environmental journalism and applies elements of environmental journalism namely ecology, social and economic development. The findings in this study indicate that only some of the elements of environmental journalism are known and applied by kumparan reporters, so it can be concluded that kumparan reporters do not understand in reporting forest fires. The misunderstanding arises from the knowledge and experience in carrying out the journalistic process, namely there is no separate environmental desk, there is a separation of angle determination from reporters and editors, and the educational background of reporters is not related to environmental knowledge. Reporters only understand environmental journalism from their experience in covering forest fires.